Suggestion on establishing curriculum system for information security major - Xiang-shen MIN; Jiu-lun FAN; Xue-feng ZHANG; Yi-xian LIU; Fang REN (网络与信息安全学报)
The problems of information security demands for professional talents and existing curriculum system setting of information security major were analyzed.A modular and hierarchical curriculum system construction scheme of information security was given under the guidance of information security professional standards promulgated by the Ministry of Education Information Security Teaching Guidance Committee.The construction of curriculum system for information security major at Xi'an University of Posts and Telecommunications was taken as the example.The modular and hierarchical optimization and implementation scheme of information se-curity undergraduate curriculum system were designed.It will be valuable to the information security profes-sional talent training.